Pengaruh Variasi Tebal Terhadap Kekuatan Lentur Pada Balok Komposit Menggunakan Response 2000 - Cahyati, Martyana Dwi (Semesta Teknika, 2016)
The tensile strength is one of disadvantage for the concrete beam. Therefore, the development of an innovation in the structural elements of the beam by using the composite material of steel and concrete is necessary. The composite system is capable of resisting expected tensile so the load capacity and moment on the beam can be increased. This study examined the effect of variations in the thickness of the cross section of the IWF's profile on flexurral moment of the composite beam. The composite beam using IWF 150x75x5x7 with variations of thickness web are 8 mm, 10 mm and 12 mm and using simply supported. The analysis using Response 2000. The results obtained for the flexural moment capacity from the variations of thickness web 8 mm thick, 10 mm and 12 mm are given respectively 236.40 kN, kN 244.63 and 252.83 kN. The results have shown that the increasing of thickness variation on the profile web IWF will increase the capacity of the composite beam bending moment. In addition, the increasing of thickness web is also affected to the increasing of stiffness on beam.